Statystyczna analiza potencjału rozwojowego powiatów ziemskich pogranicza polsko-niemieckiego jako czynnika konkurencyjności gospodarczej - Sompolska-Rzechuła, Agnieszka (Statistical Analysis of Developmental Potential of Landed Administrative Districts in Polish-German Borderland as An Economic Competitiveness Factor, 2006)
The aims of the article are: 1) a statistical analysis of developmental potential of administrative districts in Polish-German borderland, with special regard to the level of communal infrastructure and also 2) a test of creation of analysed administrative districts ranking according to developmental potential. The competitiveness of landed administrative districts which are situated in Polish-German borderland is described by many factors. One of the factors is developmental potential which is influenced by the state of communal infrastructure. The number of competing subjects on internal market is also a determinant factor socio-economic development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 319-324